SPECIAL ECONOMIC ZONES AS A FACTOR OF REGIONAL DEVELOPMENT - Abdukakhorov B.U. (Galaxy International Interdisciplinary Research Journal, 2022)
The article was described the role of special economic zones in regional development, which play an important role in the regional economic and social development of Uzbekistan. Practical proposals was given for the development of special economic zones.